TINGKAT KETERCAPAIAN ASPEK KOGNITIF SISWA KELAS VIII MADRASAH TSANAWIYAH AL-ZAYTUN PADA PEMAHAMAN SOAL BAHASA ARAB TAHUN 2025 - Anggi Laila Syarifah; Moh. Mas’ud Arifn; Iis susiawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the Cognitive Aspects of Class VIII Students of Madrasah Tsanawiyah Al-Zaytun in Understanding Arabic Language Questions in 2025 based on Bloom's revised taxonomy (C1-C6). The focus of the study is directed to describe the distribution of students' cognitive abilities at each level of thinking, without testing differences, relationships or influences between variables.Descriptive quantitative approach with observation, test and documentation data collection techniques. The main instrument is an Arabic language test designed to measure the ability of grade VIII students at various cognitive levels from remembering to creating. The population in class VIII students of MTs Al-Zaytun was 405, while the sampletaken amounted to 50 students.The results showed that students had good abilities at low cognitive levels such as remembering (C1) obtained an average success of 86% and in the aspect of understanding (C2) of 82%. The ability to apply (C3) reached 72%, indicating that students were quite capable of applying their knowledge. In the aspect of analyzing (C4), the highest result was obtained with an average of 92% indicating a strong ability to identify information and analyze images. However, at the high cognitive level, namely evaluating (C5) and creating (C6) students' abilities are still low with an average of 53%. This shows that students still have difficulty in making critical assessments and creating new sentences in an assessment manner. This finding identifies that Arabic language learning at the madrasah level still focuses on low-level thinking skills (LOTS), while higher-level thinking skills (HOTS) need to be further developed through question design and creative and applicable teaching strategies. Keywords: Cognitive aspects, Bloom's revised taxonomy, Arabic language questions, madrasah learning